Femtoampere current reference stable over atmospheric temperatures - Harrison, R; Aplin, K (2000)
Calibration of ultralow current ammeters deployed in atmospheric ion counters requires stable current references operating at high source impedance. Using standard precision components, this current reference generates equal bipolar currents of nominally ±500fA, cyclically for 32 s each. The currents were found to be stable to 2 fA over the temperature range - 20 to 20°C, typical of atmospheric conditions. The output current is delivered via a capacitor, and by arranging for the capacitor to be guarded at ground potential when the system is not generating a current, the reference can be permanently connected to an electrometer with minimal leakage. © 2000 American Institute of Physics.